119구급대원의 외상사건 경험, 외상후 스트레스와 건강증진 프로그램 요구도와의 관계 - 강미숙(Kang Mi Suk); 김영임(Kim Young Im); 근효근(Geun Hyo Geun) (지역사회간호학회지, 2017)
Purpose: This study aims to examine the relationships among experiences of traumatic events, post-traumatic stress (PTS), and the needs for health promotion programs of 119 paramedics. Methods: Experiences of traumatic events, PTS, and needs for health promotion programs were measured using a structured questionnaire. The subjects were 193 paramedics in Jeju Island. Data were analyzed using descriptive statistics, t-test and $x^2$ test. Results: The most experienced event out of the 16 different traumatic events was 'retrieve a suicide's body.' A high-risk classification of PTS was observed in 36.2% of the subjects. The rates of experiences were higher than those of the actual needs for all 26 health promotion programs. The programs reported as highly needed by respondents were stress management (75.5%) followed by exercise (74.6%) and PTS management (72.5%). Subjects with longer career periods, a fire sergeant, perceived obesity, numerous experiences of traumatic events, and in the PTS risk group had a higher need for a stress management program. Conclusion: These findings indicate that a significant number of 119 paramedics experienced PTS. They also show that onsite strategic management is strongly required. In addition, implementation of health promotion programs based on the needs of 119 paramedics is highly needed.